Mouse all-cone retina models of Cav1.4 synaptopathy - Laird, Joseph G.; Kopel, Ariel; Lankford, Colten K.; Baker, Sheila A. (Frontiers in Molecular Neuroscience, 2023)
The voltage-gated calcium channel, Cav1.4 is localized to photoreceptor ribbon synapses and functions both in molecular organization of the synapse and in regulating release of synaptic vesicles. Mutations in Cav1.4 subunits typically present as either incomplete congenital stationary night blindness or a progressive cone-rod dystrophy in humans. We developed a cone-rich mammalian model system to further study how different Cav1.4 mutations affect cones. RPE65 R91W KI; Nrl KO “Conefull” mice were crossed to Cav1.4 α1F or α2δ4 KO mice to generate the “Conefull:α1F KO” and “Conefull:α2δ4 KO” lines. Animals were assessed using a visually guided water maze, electroretinogram (ERG), optical coherence tomography (OCT), and histology. Mice of both sexes and up to six-months of age were used. Conefull: α1F KO mice could not navigate the visually guided water maze, had no b-wave in the ERG, and the developing all-cone outer nuclear layer reorganized into rosettes at the time of eye opening with degeneration progressing to 30% loss by 2-months of age. In comparison, the Conefull: α2δ4 KO mice successfully navigated the visually guided water maze, had a reduced amplitude b-wave ERG, and the development of the all-cone outer nuclear layer appeared normal although progressive degeneration with 10% loss by 2-months of age was observed. In summary, new disease models for studying congenital synaptic diseases due to loss of Cav1.4 function have been created.